Anti-HIV activity of thiosemicarbazone and semicarbazone derivatives of (±)-3-menthone - Mishra V.; Pandeya S.N.; Pannecouque C.; Witvrouw M.; De Clercq E. (My University, 2025)
A series of thiosemicarbazones and semicarbazone derivatives of (±)-3-menthone have been synthesized and their anti-HIV activity evaluated against HIV-1(IIIB) and HIV-2 (ROD). The studies revealed that maximum protection is offered by chlorosubstituted derivatives 2 and 7 against HIV-1 (IIIB) and HIV-2 (ROD).